Light discomfort thresholds under different lighting conditions in healthy subjects and dry eye patients - Filippo Lixi; Giulia Coco; Claudia Corda; Edoardo Villani; Alessandra Curci; Carina Slidsborg; Giuseppe Giannaccare (Scientific Reports)
Abstract Light-related visual disturbances are common symptoms among patients with dry eye disease (DED) but difficult to be evaluated in the clinical practice. This cross-sectional, multicenter, controlled study aimed at comparing light discomfort thresholds in healthy individuals and patients with DED, and to further correlate thresholds with ocular surface parameters. The Lumiz 100 device (Essilor International, Paris, France) was employed to measure light discomfort thresholds in 25 patients with DED and 25 sex- and age-matched healthy subjects under different lighting conditions: continuous warm, continuous cold and flashing warm. Participants were instructed to press a button twice to signal discomfort levels as “just perceptible” and “really disturbing”. The mean of the two values was calculated for each lighting condition. DED patients exhibited lower discomfort thresholds for all measurements compared to controls (continuous warm: 2.81 ± 0.56 log10[lux] vs. 3.47 ± 0.51 log10[lux], continuous cold: 2.78 ± 0.54 log10[lux] vs. 3.48 ± 0.50 log10[lux], flashing warm: 2.54 ± 0.53 log10[lux] vs. 3.12 ± 0.69 log10[lux], all p ≤ 0.004). A significant negative correlation was found between total light sensitivity threshold and ocular discomfort symptoms in patients with DED (r=-0.499, p = 0.011). Conversely, no significant correlation was found between light thresholds and the other ocular surface parameters. These findings show that DED patients have a higher light sensitivity than healthy subjects.